Mitchell, Barbara. Photograph of Barbara Mitchell, her father William Druken, and a doll outside fence in the front yard of house on Druken's Lane from Barbara Mitchell's personal photograph collection. - Jarvis, Dale (1945)
Barbara Mitchell, Barbara's father William Druken, and doll outside fence in front yard of house on Druken Lane. Mary Ann (Hall) Druken's house in background.